PENGGUNAAN DIVERSI DALAM PERKARA TINDAK PIDANA NARKOTIKA OLEH ANAK (STUDI PUTUSAN PENGADILAN NEGERI SIBUHUAN NOMOR 2/PID.SUS-ANAK/2022/PN SBH): Use Of Diversion In The Case Of Narcotics Offences By Children (Study Of The Sibuhuan Court Number2/Pid.Sus-Anak/2022/Pnsbh) - David Bueno; Setiyono (Reformasi Hukum Trisakti, 2025)
The criminal justice system is often considered ineffective and can have negative impacts on children, such as stigmatization and dehumanization. Diversion aims to protect children from the adverse effects of criminal justice and support their development. The problem is about, the use of diversion efforts in cases of drug crimes committed by children, with a case study of Sibuhuan District Court Decision Number 2/Pid. Sus-Anak/2022/Pn.Sbh. The result and conclusion; still not maximized in its application, in this case the child who committed a narcotics crime has met the requirements for diversion efforts but this was not pursued during the process, this study also examines the legal consequences of not applying diversion efforts in the examination process in court, where there are no legal consequences for law enforcement officials, the research method used is a normative approach with analysis of applicable laws and regulations and literature studies.